A systematic review and meta-analysis of the impact of left bundle branch area pacing on right ventricular function - Lei Yin; Lianxia Wang; Jiankang Meng; Qian Liu; Yan Zhang; Yanlei Zhao; Mingwang Li; Ling You (Frontiers in Cardiovascular Medicine)
ObjectiveThis study aims to systematically evaluate and perform a meta-analysis on the effects of LBBAP on right ventricular (RV) function by collecting data on Right Ventricular Fractional Area Change (RV-FAC), Tricuspid Annular Plane Systolic Excursion (TAPSE), Interventricular Mechanical Delay (IVMD), and the incidence of tricuspid regurgitation (TR) worsening in Left bundle branch area pacing (LBBAP) patients.MethodsA comprehensive search was conducted for studies published from the establishment of the respective databases until October 2024 in PubMed, Embase, Web of Science, and the Cochrane Library. After screening and data extraction, the Newcastle-Ottawa Scale was used for the quality assessment of the included cohort studies, and meta-analysis was performed using R software. The effect size was estimated using either a random-effect model or a fixed-effect model, with odds ratio (OR) and mean difference (MD).ResultsA total of 14 studies were included, analyzing 1,555 LBBAP patients. The meta-analysis revealed that compared with intrinsic conduction, LBBAP implantation significantly improved RV-FAC (MD = 1.93; 95% CI: 0.64–3.23, P = 0.0034) and TAPSE (MD = 1.57; 95% CI: 1.07–2.06, P < 0.0001). Compared to the RVP group, LBBAP implantation significantly shortened IVMD (MD = −21.27; 95% CI: −31.33 to −11.22, P < 0.0001). For patients with RV dysfunction or right bundle branch block (RBBB), LBBAP implantation also significantly reduced IVMD (MD = −31.31; 95% CI: −37.10 to −25.52, P < 0.0001). The incidence of TR worsening within one year after LBBAP was approximately 8%, increasing to 23% beyond one year.ConclusionThis meta-analysis demonstrates the superiority of LBBAP over intrinsic conduction in improving RV systolic function. Compared to RVP, LBBAP significantly enhances biventricular synchronization. Furthermore, LBBAP also improves ventricular synchronization in patients with RV dysfunction or RBBB.